Ursus arctos Linnaeus 1758 - W. Christopher Wozencraft (Smithsonian Institution Press, 1993)
Ursus arctos Linnaeus, 1758. Syst. Nat., 10th ed., 1:47. TYPE LOCALITY: "sylvis Europae frigidae" restricted by Thomas (1911a) to, "Northern Sweden." DISTRIBUTION: Formerly, NW Africa, all of the Palearctic from W Europe, Near and Middle East through N Himalayas to W and N China and Chukot (Russia); Hokkaido (Japan); W North America, north from N Mexico. STATUS: CITES - Appendix I as U. arctos (Mexico, Bhutan, China, and Mongolia populations), U. a. isabellinus, and U. a. pruinosus; otherwise Appendix II. U.S. ESA - Endangered as U. a. arctos in Italy, U. a. nelsoni in Mexico, and U. a. pruinosus; Threatened as U. a. horribilis in the USA (48 conterminous states); IUCN - Extinct as U. a. nelsoni. SYNONYMS: absarokus Merriam, 1914; alascensis Merriam, 1896; albus Gmelin, 1788; alexandrae Merriam, 1914; alpinus Fischer, 1814; andersoni Merriam, 1918; annulatus Billberg, 1827; apache Merriam, 1916; argenteus Billberg, 1827; arizonae Merriam, 1916; atnarko Merriam, 1918; aureus Fitzinger, 1855; badius Schrank, 1798; baikalensis Ognev, 1924; bairdi Merriam, 1918; beringiana Middendorff, 1853; bisonophagus Merriam, 1918; bosniensis Bolkay, 1925; brunneus Billberg, 1827; cadaverinus Eversmann, 1840; californicus Merriam, 1896; canadensis Merriam, 1914; candescens Hamilton-Smith, 1827; caucasicus Smirnov, 1919; caurinus Merriam, 1914; cavifrons Heude, 1901; chelan Merriam, 1916; chelidonias Merriam, 1918; cinereus Desmarest, 1820; collaris Cuvier and Geoffroy Saint-Hilarie, 1824; colusus Merriam, 1914; crassodon Merriam, 1918; crassus Merriam, 1918; cressonus Merriam, 1916; crowtheri Schinz, 1844; dalli Merriam, 1896; dusorgus Merriam, 1916; eltonclarki Merriam, 1914; ereunetes Merriam, 1918; eulophus Merriam, 1904; euryrhinus Nilsson, 1847; eversmanni Gray, 1864; eximius Merriam, 1916; falciger Reichenbach, 1836; ferox Temminck, 1844; formicarius Billberg, 1828;/mscms Gmelin, 1788; grandis Gray, 1864; griseus Kerr, 1792; gyas Merriam, 1902; henshawi Merriam, 1914; holzworthi Merriam, 1929; hoots Merriam, 1916; ...